Exploration on Varying Patterns of Morphological Features and Quality of Armeniacae Semen Amarum in Rancid Process Based on Colorimeter, Electronic Nose, and GC/MS Coupled With Human Panel - Shao, Yuanyang; Chen, Huirong; Lin, Hongxin; Feng, Huishang; Gong, Jianting; Cao, Guangzhao; Hong, Weifeng; Yao, Yuebao; Zou, Huiqin; Yan, Yonghong (Frontiers in Pharmacology, 2022)
In recent years, the domestic and international trade volume of Chinese medicinal materials keeps increasing. However, different kinds of deterioration are prone to occur, for instance, get moldy or rancid, which not only cause a huge waste of CMMs resources, but also pose a great threat to clinical medication safety and public health. In this study, as a medicine and food material that is easy to get rancid, Armeniacae Semen Amarum was chosen as research objective and experimental ASA samples of different rancid degrees were collected. Then kinds of analytical methods and technologies were applied to explore the changing rules of ASA quality and figure out the key indicators for quality evaluation of ASA in rancid process, including human panel, colorimeter, electronic nose and GC/MS. This project aims to analyze the correlation between the external morphological features and the inner chemical compounds, to find out the special components from "quantitative change" to "qualitative change” in the process of "getting rancid", and to discover the dynamic changes of the above-mentioned key indicators at different stages of rancidness. The results showed since ASA samples began to get rancid with the extension of storage time, morphological features, namely surface color, smell, etc., changed significantly, and the degree of rancidness further deepened at the same time. Based on macroscopic identification accomplished via human panel, ASA samples with varying degrees of rancidness were divided into four groups. The result of colorimeter analysis was in agreement with human panel, as well as determination of amygdalin content and peroxide value. Moreover, there were obvious differences in the amygdalin content and peroxide value among ASA samples of different rancid degrees. With the deepening of the degree of rancidness, the content of amygdalin decreased while the peroxide value increased significantly. The rancid degree of ASA has a negative correlation with the amygdalin content, and positive with the peroxide value. The newly-discovered nonanal and 2-bromopropiophenone in rancid ASA samples may be the key components of "rancidity smell", and these two components would be the exclusive components that trigger "quantitative change" to "qualitative change" in the process of rancidness of ASA.